Alterations of the salivary microbiome in obstructive sleep apnea and their association with periodontitis - Li, Jiong; Gao, Jike; Ma, Yunxia; Li, Wuli; Chen, Xiangru; Li, Zhenhua; Zhang, Xiujun (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveObstructive sleep apnea (OSA) and periodontitis have demonstrated epidemiological and clinical associations. This study aimed to characterize salivary microbiome alterations in patients with OSA, periodontitis, and their comorbidity (OSA+PD), and to explore potential microbial markers.Materials and methodsThis cross-sectional study included 125 adults divided into four groups: healthy controls (H, n=26), patients with OSA (OSA/O, n=42), patients with periodontitis (PD/P, n=15), and patients with OSA and periodontitis (OSA+PD/OP, n=42). Participants underwent nocturnal polysomnography and comprehensive periodontal examinations. Saliva samples were collected and analyzed using 16S ribosomal DNA gene sequencing to evaluate microbial distribution and community structure across groups. Receiver operating characteristic (ROC) curves were generated for key taxa combining with clinical indicators, and the area under the curve (AUC) values were calculated to assess diagnostic relevance.ResultsOral microbial diversity was significantly altered in OSA, PD, and OSA+PD groups. Alpha diversity was reduced in all patient groups compared to healthy controls, with the periodontitis group showing the highest diversity and evenness. Beta diversity revealed that periodontitis having the strongest impact and the comorbid group exhibiting intermediate characteristics between OSA and periodontitis. Key taxa, including Tannerella, Treponema, Prevotella, Slackia, and Streptococcus constellatus, exhibited significant intergroup differences. BugBase phenotype analysis revealed an increased abundance of aerobic and a reduced presence of anaerobic microbial profiles in the OSA and OSA+PD groups. Additionally, Rothia and Micrococcaceae were more abundant in the OSA group, regardless of periodontal status. Receiver operating characteristic (ROC) analysis indicated that Rothia and Parvimonas reliably differentiated between OSA and OSA+PD (AUC=0.715, 0.702) and also between periodontitis and OSA+PD (Rothia: AUC=0.879).ConclusionOSA is associated with distinct changes in salivary microbiota, including reduced microbial richness and altered functional profiles, which may contribute to early periodontal dysbiosis. Rothia has been identified as a potential microbial biomarker for OSA-related periodontitis, while Rothia and Parvimonas may play a key role in periodontitis-related OSA. However, as this is a cross-sectional study, causal relationships and the predictive value of microbial biomarkers remain to be confirmed in longitudinal studies. These results highlight the need for integrated management of OSA and periodontitis and suggest microbial profiling as a useful diagnostic tool.